BODY IMAGE IN CHILDREN WITH CANCER - Bharathan, Anitha; Antony, Sherin (International Journal of Psychosocial Rehabilitation, 2022)
Children with cancer face a variety of difficulties. This review looked at studies that looked at how children with cancer felt about their bodies using qualitative methodologies. Frequent hospital visits, medicines, and invasive medical procedures disturb the usual life and routine of children with cancer, forcing them to cope with changes in their physical appearance as well as anxieties about their future. The body images are changed from one person to another because it is subjective in nature. The human characteristics such as self-protective tactics, self-identity loss, body distance and support has been reflected via the metasyntheses. Children with cancer face a variety of issues related to changes in their body image. Treatment courses that are repeated often result in the loss of a regular, organized existence, as well as alterations in interpersonal interactions. Individuals with cancer adopt selfprotective, coping techniques in reaction to changes in their body image. If the children suffered by cancer their body faces numerous changes which will affect their future outlook.